2021
DOI: 10.1242/dev.199208
|View full text |Cite
|
Sign up to set email alerts
|

Concerted morphogenesis of genital ridges and nephric ducts in the mouse captured through whole-embryo imaging

Abstract: During development of the mouse urogenital complex, the gonads undergo changes in three-dimensional structure, body position, and spatial relationship with the mesonephric ducts, kidneys, and adrenals. The complexity of genital ridge development obscures potential connections between morphogenesis and gonadal sex determination. To characterize the morphogenic processes implicated in regulating gonad shape and fate, we used whole embryo tissue clearing and light sheet microscopy to assemble a time course of gon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…1I). SLCs express CE-derived somatic cell markers such as Nr5a1 , Wt1 , and Gata4 , but also Pax8 , a marker of cells of the mesonephric tubules, the rete testis, and rete ovarii ( 17 , 25 ). In contrast, SLCs do not express Dmrt1 and Pax2 , a well-known marker of mesonephric tubules (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1I). SLCs express CE-derived somatic cell markers such as Nr5a1 , Wt1 , and Gata4 , but also Pax8 , a marker of cells of the mesonephric tubules, the rete testis, and rete ovarii ( 17 , 25 ). In contrast, SLCs do not express Dmrt1 and Pax2 , a well-known marker of mesonephric tubules (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Spearman’s correlation analysis and hierarchical clustering revealed that the transcriptome of the early and late SLC populations share similarities with those of other cell types of the supporting lineage, such as granulosa, pre-supporting and Sertoli cells ( Figure 1I ). SLCs express CE-derived somatic cell markers such as Nr5a1 , Wt1 , and Gata4 , but also Pax8 , a marker of cells of the mesonephric tubules, the rete testis and rete ovarii ( 21, 29 ). In contrast, SLCs do not express Pax2, a well-known marker of mesonephric tubules ( 30 ) ( Figure 1J ).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the optimal angles to assess ovary morphology, we first performed immunostaining of whole XX embryos at E14.5 with antibodies against FOXL2, which is expressed in pre-granulosa cells and serves as a marker of the gonadal domain, and antibodies against PAX8, which is expressed in the epithelium of the reproductive ducts and cells of the developing kidney. These samples were cleared using iDISCO and imaged with lightsheet microscopy (Bunce et al, 2021; Renier et al, 2014). We generated 3D models of the labelled structures using isosurface segmentation to provide a morphological view of the urogenital complex in situ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1B). A recent study combining contextual 3D images of the developing gonads in the whole embryo with quantitative morphometric analysis showed that the entire genital ridge rotates inward from E10.5 to E12.5 (Bunce et al, 2021), thus by E12.5 the gonads appear on the medial aspect of the mesonephros. Consistent with these observations, at E14.5 the reproductive ducts were located lateral to the gonads, which were oriented towards each other in the medial axis (Fig.…”
Section: S1a Movie S1)mentioning
confidence: 99%
See 1 more Smart Citation